Association of human disturbance and gastrointestinal parasite infection of yellow baboons in western Tanzania - Mason, Bethan; Piel, Alex K; Modrý, David; Petrželková, Klára J; Stewart, Fiona A; Pafčo, Barbora (PloS one, 2022)
Human disturbance is an ongoing threat to many wildlife species, manifesting as habitat destruction, resource overuse, or increased disease exposure, among others. With increasing human: non-human primate (NHP) encounters, NHPs are increasingly susceptible to human-introduced diseases, including those with parasitic origins. As such, epidemiology of parasitic disease is becoming an important consideration for NHP conservation strategies. To investigate the relationship between parasite infections and human disturbance we studied yellow baboons (Papio cynocephalus) living outside of national park boundaries in western Tanzania, collecting 135 fresh faecal samples from nine troops occupying areas with varying levels of human disturbance. We fixed all samples in 10% formalin and later evaluated parasite prevalence and abundance (of isotrichid ciliates and Strongylida). We identified seven protozoan and four helminth taxa. Taxa showed varied relationships with human disturbance, baboon troop size and host age. In four taxa, we found a positive association between prevalence and troop size. We also report a trend towards higher parasite prevalence of two taxa in less disturbed areas. To the contrary, high levels of human disturbance predicted increased abundance of isotrichid ciliates, although no relationship was found between disturbance and Strongylida abundance. Our results provide mixed evidence that human disturbance is associated with NHP parasite infections, highlighting the need to consider monitoring parasite infections when developing NHP conservation strategies.
Keywords: Feces; gastrointestinální nemoci; ekosystém; Gastrointestinal Diseases; Helminthiasis, Animal; cizopasní červi; helmintózy zvířat; parazitární nemoci střev; Monkey Diseases; zvířata; feces; Tanzanie; lidské činnosti; Humans; Papio cynocephalus; Human Activities; Helminths; Tanzania; Intestinal Diseases, Parasitic; Ecosystem; nemoci opic; lidé; Animals